The Committee Against Torture tackles violence against women: A conceptual and political journey - Nora Sveaass; Felice Gaer (Torture)
In this article, we will examine how the official treaty monitoring body, the Committee against Torture, demonstrated that violence against women was indeed a serious human rights problem that fell squarely within the preview of the Convention against Torture. Because States parties to the Convention are required to report about their compliance with the Convention routinely, the Committee developed a substantial database on national practices and policies. In the course of examining these periodic reports of States parties, and then consolidating findings and conclusions into two general comments, the UN Committee Against Torture integrated violence against women in its jurisprudence on torture and ill-treatment by showing that existing provisions could and did incorporate the obligation to protect against and provide redress for torture and ill-treatment directed against women. Initiatives to raise these issues show how the Committee “placed the range of gender violence—from public to private – squarely within the frame of the Torture Convention” (Copelon, 2008, 242). The article will recall how the adoption of two general comments to the Convention firmly integrated gender-based violence as a subject of concern under the Convention: General comment no 2 (2008) addressed Article 2 on the State obligation to prevent torture and ill-treatment and General comment no 3 (2012) focused on Article 14 which concerns the obligation to provide redress to victims of torture. Both authors have been members of the Committee during these important years, and it is our aim to provide an overview of the significant processes and decisions taken by the CAT that resulted in the strengthening of the  Committee’s inclusiveness and comprehensiveness in the struggle to prevent torture. Finally, we will reflect on some future challenges faced by main anti-torture body/ies as part of global efforts to fight violence against women.